Fratura da diáfise de úmero associada a luxação de cotovelo e fratura do terço distal do antebraço: relato de caso - Alencar Neto, Jonatas Brito (2018)
Humeral shaft fractures combined with elbow dislocation and fracture of the distal third of the bones of the forearm are uncommon. No description of this simultaneous association has been found in the same patient. This report describes a case that occurred in a 13 year‐old boy who suffered a fall from a height of approximately three meters, and was admitted to a trauma hospital. Radiographs showed ipsilateral humeral shaft fracture combined with elbow dislocation and fracture of the distal‐third of the bones of the forearm. Under general anesthesia, the injuries were readily reduced by closed manipulation, obtaining a satisfactory reduction of the injuries. Following this, an antebrachiopalmar splint and an arm sling for humerus diaphyseal fracture treatment were used. After one week, the patient presented non‐alignment of the diaphyseal fracture of the humerus, and was submitted to surgical treatment with flexible retrograde intramedullary nailing, antebrachiopalmar cast, and sling.